Engineering mechanics : dynamics - Meriam, J. L. [ (James L.)]; Kraige, L. G. [ (L. Glenn)] (Wiley, 2013)
Known for its accuracy, clarity, and dependability, Meriam has provided a solid foundation of mechanics principles for more than 60 years. The text continues to help students develop their problem-solving skills with an extensive variety of engaging problems related to engineering design